Performance Analysis of Smart Energy Monitoring Systems in Real-time - Govindarajan, R.; Meikandasivam, S.; Vijayakumar, D. (Engineering, Technology & Applied Science Research, 2020)
The use of smart energy monitoring systems in buildings offers significant potential for energy saving. The introduction of a new kind of energy monitoring system is essential in the consumer-side in order to meet the demands of energy conservation. In this paper, four energy monitoring systems based on advanced wireless technology are proposed. The design and implementation of the smart real-time energy monitoring systems is analyzed with respect to their performance. The proposed systems utilize advanced wireless technologies like the Zigbee module, Internet of Things (IoT), Android Mobile Apps, and cloud computing for interfacing the information between the meters and the consumer end. A digital power meter is installed in the main panel, interfaced with a communication gateway and parameters such as voltage, current, power, power factor, and the harmonics of household appliances are measured in real-time. These systems provide power consumption details to the consumer and allow interacting with them by giving instant data such as live power tracking, identification of abnormal patterns of energy usage, energy bill estimation, and energy usage information.